GRUPO DE SUPORTE ÀS FUNÇÕES PARENTAIS - GRUPO DE GESTANTES E DE PAIS - ATIVIDADE DE EXTENSÃO UNIVERSITÁRIA - Dreher, Daniela Z.; Campos, Iris F. A.; Sand, Isabel C. P. V. d.; Tessari, Ana M. B.; Aozane, Fabieli; Sczareski, Fernanda A.; Gross, Caroline; Tusset, Josiane; Rios, Karina R.; Aozane, Fabieli (Salão do Conhecimento, 2013)
Resumo